Pragmatemas de precaución relacionados con el consumo de productos farmacéuticos en los países de habla hispana - Lisowska, Monika (Studia Romanica Posnaniensia, 2025)
This article analyzes the precautionary pragmatemes currently employed by pharmaceutical companies to prevent the irresponsible consumption of over-the-counter medications. The selected sample consists of eighty audiovisual advertisements for these medications, meant for eleven Spanish-speaking countries. The analysis shows that possible diatopic differences do not affect the lexical level and only minimally affect the morphosyntactic level. What truly distinguishes these pragmatemes in the Spanish-speaking world is the discursive level, specifically the type of recommendations conveyed in the advertisements, which often are the result of the national laws of the national legal regulations of the respective country.